2010
DOI: 10.3348/kjr.2010.11.4.425
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Disease in Asymptomatic Young Adults: Its Prevalence According to Coronary Artery Disease Risk Stratification and the CT Characteristics

Abstract: ObjectiveWe aimed at evaluating the prevalence and CT characteristics of occult coronary artery disease (CAD) in young Korean adults under 40 years of age by performing coronary CT angiography (CCTA).Materials and MethodsWe retrospectively enrolled 112 consecutive asymptomatic subjects (90 men, mean age: 35.6 ± 3.7 years) who underwent CCTA as part of a general health evaluation. We classified the subjects into three National Cholesterol Education Program risk categories and we assessed the plaque characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The prevalence of occult CAD in 112 asymptomatic young individuals, less than 40 years of age, was found to be 11% (9 had single vessel disease and 3 had double vessel disease) in a study done in Korea. The occult CAD in these individuals was defined by performing coronary CT angiography[18]. …”
Section: Trends In Epidimiological Profilementioning
confidence: 99%
“…The prevalence of occult CAD in 112 asymptomatic young individuals, less than 40 years of age, was found to be 11% (9 had single vessel disease and 3 had double vessel disease) in a study done in Korea. The occult CAD in these individuals was defined by performing coronary CT angiography[18]. …”
Section: Trends In Epidimiological Profilementioning
confidence: 99%
“…Early adult levels of modifiable risk factors at baseline predicted the presence of CACS by ages 33 to 45 years [95]. Similar findings between the relationship between the early development of coronary artery calcification and CCTA in young adults with established risk factors have been reported [96][97][98]. Future studies will need to be completed to further address the associations between childhood risk factors and disease end points and the need for earlier risk assessment.…”
Section: Coronary Artery Calcium Scoring and Ccta In The Extremes Of Agementioning
confidence: 53%
“…Historically, screening has included echocardiography with variable follow‐up after the completion of therapy. The median age of patients with CAD in this study was 40 years, which is significantly younger for a diagnosis of CAD compared with a noncancer population, suggesting that this patient population requires more vigilant screening. Multidetector CCTA is a potentially useful screening modality for these patients.…”
Section: Discussionmentioning
confidence: 78%
“…In an investigation of adults without known CAD who were evaluated for nonemergent chest pain, researchers reported sensitivity, specificity, and positive and negative predictive values of 94%, 83%, 48%, and 99%, respectively, for CCTA in detecting ≥70% stenosis . Ha et al used CCTA to evaluate healthy young adults (aged ≤40 years) with no history of cancer and found that 11% of study participants had evidence of occult CAD, but no cases were obstructive. In the similarly young population in the current study, 10% of patients had obstructive disease; an additional 29% had nonobstructive lesions.…”
Section: Discussionmentioning
confidence: 99%